Measuring Accountability for Filling the Acting Regional Heads in Indonesia: Menakar Akuntabilitas Pengisian Penjabat Kepala Daerah di Indonesia - Kurniawan, Muhammad Fitra; Al Faruq, Muhammad Hamzah; Ruhpinesthi, Garuda Era (Jurnal Konstitusi, 2023)
Before the regional head elections, the Minister of Home Affairs(Mendagri) appoints acting regional heads, sparking discussionsabout accountability. This study aims to analyze the development ofregulations for appointing acting regional heads and their implicationsfor accountability. The research, conducted as normative juridicalresearch using secondary data, reveals two key findings. Firstly, thereare three distinct aspects differing in the process of appointing actingregional heads: the reasons for filling the position, the criteria forbecoming acting, and the extended term of the acting position withoutaccountability. Secondly, the lack of accountability in the appointmentprocess has implications, including the potential for acting regionalheads lacking understanding of the region, the presence of actingregional heads driven by political interests, their limited experienceand increased vulnerability to political influence, and the risk ofunsustainable programs initiated by the previous regional head.